Hybrid Governance and Policy Frameworks as Catalysts for Biotechnology Innovation: Global Lessons for Emerging Economies - Arainy, Corizon Sinar; Sunarno (Novatio : Journal of Management Technology and Innovation, 2025)
Biotechnology is increasingly central to global innovation, with progress depending on effective collaboration between universities, industry, and policy frameworks. This study aims to examine institutional and policy drivers of university–industry collaboration (UIC) in biotechnology and identify models that accelerate commercialization and sustainable growth. Using qualitative comparative analysis (QCA) on four cases—SynbiCITE (UK), Bio Innovation Hub (Australia), Panjab University (India), and Oxford Science Enterprises (UK)—data were drawn from reports, policy documents, and innovation databases (WIPO, OECD, GEM). Results show that hybrid governance, flexible funding, transparent intellectual property (IP) frameworks, and targeted policy incentives shorten commercialization timelines, raise start-up survival above 65%, and boost joint patenting activity. University-linked venture capital provides patient capital and mentorship, while mission-driven R&D policies and balanced IP reforms enhance national alignment and innovation outputs. These findings suggest that integrated governance and policy strategies can foster competitive biotechnology ecosystems, and for emerging economies, adapting such models to local contexts offers pathways to accelerated innovation and long-term societal benefits.